Respon Pertumbuhan Tanaman Jengger Ayam Merah Celosia plumosa (Voss) Burv. Pada Tanah Tercemar Logam Berat Kadmium (Cd) - Juhriah Juhriah; Sri Suhadiyah; Reski Mandasari (Universitas Hasanuddin, 2017)
Research on the growth response of Red Cockscomb Plant Celosia plumosa (Voss) Burv. on contaminated soils heavy metal Cadmium (Cd) has been carried out from March to July 2016 in Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University. The aims of this research is to find out the growth response of red Cockscomb Celosia plumosa (Voss) Burv. on the ground of cadmium heavy metals (Cd) and its potential as phytoremediation agent of Cd metal on soil. The study was arranged in a Randomized Block Design, 4 treatments (source of sewage sludge land, garden soils, rice field and landfill or final waste disposal) and 3 groups. The cadmium content analysis was performed at Centerfor Health Laboratory of Makassar, South Sulawesi, using Atomic Absorption Spectrophotometer (AAS). The data were tested by F test, the different significant result was followed by the Smallest Differential Test (SDT). The results of the analysis showed that the growth of Red Cockscomb Plant Celosia plumosa (Voss) Burv. plants able to live better (higher plants, more leaves and wet or dry weight higher) on the land from landfills (final waste disposal ) is compared to the other three sources of land.